2004
DOI: 10.1182/blood-2004-01-0207
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic consequences of Bruton tyrosine kinase deficiency in myeloid lineages lead to poor inflammatory responses

Abstract: Bruton tyrosine kinase (Btk), a nonreceptor-associated tyrosine kinase of the Tec family, appears to participate in many myeloid cell functions. We show that macrophages from X-linked immunodeficient (XID) mice lacking functional Btk cannot generate efficient bursts of reactive oxygen intermediates (ROIs). The induction of apoptotic cell death by inflammatory stimuli is also enhanced in XID macrophages. Phagocytosis of bacterial particles is only marginally affected in them.In vivo, XID mice show reduced sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 47 publications
7
120
1
1
Order By: Relevance
“…The lack of ibrutinib effect on monocyte/macrophage-mediated phagocytosis is in agreement with Mangla et al (32), who found that phagocytosis of heat-killed fluoresceinated E. coli was not affected in macrophages from Xid mice. This lack of effect is likely not due to insufficient levels of ibrutinib because we tested with levels of 1 and 10 M, and we saw effective blocking of Btk phosphorylation even at 1 M. In addition, it has been shown that as little as 1-10 nM is sufficient to block Fc␥R-mediated cytokine production in monocytes and THP-1 cells (19), which suggests that Btk kinase activity (and, most notably, its downstream Ca 2ϩ mobilization) is not required for phagocytosis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The lack of ibrutinib effect on monocyte/macrophage-mediated phagocytosis is in agreement with Mangla et al (32), who found that phagocytosis of heat-killed fluoresceinated E. coli was not affected in macrophages from Xid mice. This lack of effect is likely not due to insufficient levels of ibrutinib because we tested with levels of 1 and 10 M, and we saw effective blocking of Btk phosphorylation even at 1 M. In addition, it has been shown that as little as 1-10 nM is sufficient to block Fc␥R-mediated cytokine production in monocytes and THP-1 cells (19), which suggests that Btk kinase activity (and, most notably, its downstream Ca 2ϩ mobilization) is not required for phagocytosis.…”
Section: Discussionsupporting
confidence: 80%
“…This results in an arginine-to-cysteine change within the N-terminal region of Btk (37,38), which contains the pleckstrin homology region that interacts with protein kinase C (39). It has been shown previously that peritoneal macrophages from Xid mice do not show defects in their ability to ingest heat-killed Escherichia coli (32). Regarding Fc␥R-mediated phagocytosis, the xid gene was able to rescue the decreased ability of peritoneal macrophages from autoimmune-prone NZB mice to ingest opsonized sheep red blood cells (40).…”
Section: Ibrutinib Suppresses Fc␥r-mediated Cytokine Production But Nmentioning
confidence: 99%
“…injection of 4% thioglycolate broth (Himedia). At 72 h postinjection, cells were harvested from the peritoneum and macrophages were isolated by plastic adherence as described previously (16). Purified populations were Ͼ90% CD11b ϩ .…”
Section: Cell Preparations Activation Protocols and Death Assaysmentioning
confidence: 99%
“…BTK is a cytoplasmic, nonreceptor tyrosine kinase belonging to the TEC family of tyrosine kinases (7) and is expressed in all stages of B cell development, with the exception of long-lived, antibody-producing plasma cells (8,9). Besides B lymphocytes, many other hematopoietic cells also express BTK (5,(8)(9)(10), but clinically relevant functional impairment seems to be confined to this lineage. Thus, the severe clinical outcome of BTK mutations demonstrates the essential role of BTK already occurring in pre-B cell receptor signaling, which is a determinant for proliferation, differentiation, and survival of the early B cell stages (3,11,12).…”
Section: Introductionmentioning
confidence: 99%